Arrears to the IMF : A Ghost of the Past? - Oeking, Anne (IMF Working Papers; Working Paper ;, 2016)
In this paper, we consider incidences of arrears to the IMF, focusing on protracted arrears cases and attempt to identify determinants of their occurrence. We use narrative and formal methods. In addition, we analyze determinants of the duration of arrears. We find that previous arrears, reserves coverage, and institutional quality are among the main determinants of arrears. In addition, we identify a role for political developments, including civil unrest, which make arrears more likely to arise and to last longer. We conclude that improved macroeconomic conditions and turnaround of political fortunes would help to clear the currently remaining protracted arrears cases.